Tunable Environment-Enhanced Mid-Infrared Absorber Based on Voltage Modulation - Gongli Xiao; Zifan Lai; Hongyan Yang; Bing Wang; Haiou Li (IEEE Photonics Journal)
In this paper, we propose a design of a mid-infrared Metamaterial Absorber (MIMA). The MIMA is composed of a thin metamaterial nanostructure of period array of cross-circular structure of Ti with continuum graphene layer and bottom film is Al substrate, the middle dielectric layer is a stack of Si3N4 and SiO2. The coupling of surface plasmon resonance (SPR) of graphene, metal Ti and dielectric layers and the intrinsic absorption of the material enhance broadband absorption. The MIMA maintains 97% average absorption in the 3.8∼6.5 μm in the background refractive index of 1.33. MIMA maintains 80% average absorption within an incidence angle of 50 and it is polarization insensitive. Dynamic tuning of the MIMA absorption bandwidth by changing the Fermi energy level of graphene by applying a voltage to the graphene surface. The absorption bandwidth can broaden in complex environments (water, ice, alcohol). The proposed research shows excellent applications in thermal emitter and photocatalysis, infrared camouflage in complex environment.